2016
DOI: 10.18632/aging.101050
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β and NF-κB signaling pathway crosstalk potentiates corneal epithelial senescence through an RNA stress response

Abstract: The corneal epithelium plays important roles in the maintenance of corneal transparency for good vision, and acts as a protective barrier against foreign insults. Structural and functional changes with aging in the corneal epithelium have been documented. Here we found that transforming growth factor-β (TGF-β) is highly expressed in the elderly donor corneal epithelium, as are senescence-associated genes, such as p16 and p21. In human corneal epithelial cell (HCEC) models, TGF-β induces cellular senescence, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…Notwithstanding our findings in this study, TGF‐β induces cellular senescence in human corneal epithelial cells in cooperation with NF‐kB signals . Consistent with this, we already reported that TNF‐α signals cooperate with TGF‐β to induce the EMT in lung cancer A549 cells harboring active K‐Ras mutation, and NF‐kB inhibitor blocks the EMT .…”
Section: Discussionsupporting
confidence: 91%
“…Notwithstanding our findings in this study, TGF‐β induces cellular senescence in human corneal epithelial cells in cooperation with NF‐kB signals . Consistent with this, we already reported that TNF‐α signals cooperate with TGF‐β to induce the EMT in lung cancer A549 cells harboring active K‐Ras mutation, and NF‐kB inhibitor blocks the EMT .…”
Section: Discussionsupporting
confidence: 91%
“…Corneal allografts and MDSCs were lysed in RIPA buffer (Beyotime, Beijing, China) with a protease inhibitor cocktail (Millipore), respectively. Western blot was performed as described previously ( 24 ). The membranes were probed with anti-GAPDH (KC-5G5, Kangchen) and anti-iNOS (ab15323, Abcam) primary antibodies and subsequently reacted with HRP-conjugated secondary antibodies (Pierce, 1:3,000), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The TGF-β protein has three different isoforms (1-3), located in the extracellular matrix and can regulate several biological cell functions such as proliferation, differentiation, migration, and survival, playing pivotal role in the morphogenesis and homeostasis [ 10 ]. This protein is expressed in different tissues including brain [ 9 ], tumor [ 11 ], corneal epithelium [ 12 ] and muscle [ 13 ]. There are some evidences that links the TGF-β1 levels with obesity and aging in rodents and humans [ 9 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%